Driving Firm Performance through Product Differentiation Strategy and Service Innovation: Evidence from Nepal’s Commercial Banking Sector - Thapa, Bala Ram; Chalise, Mahananda (International Journal of Atharva, 2025)
Background: In Nepal’s commercial banking industry, increased competition has led companies to adopt product differentiation strategies to enhance their market position. However, the impact of these strategies on performance, particularly from an innovation perspective, has not been thoroughly explored. Objective: This study explores how product differentiation strategies influence firm performance, placing special focus on the mediating role of service innovation in this connection. Methods: This study utilised Smart PLS-SEM analysis to examine the suggested relationships, drawing on data from 105 senior executives from 14 different commercial banks. Findings: The analysis reveals that simply differentiating products does not directly enhance the performance. Instead, it significantly boosts service innovation, which in turn positively influences firm performance, thereby confirming the full mediation effect. Conclusion: Service innovation plays a vital role in converting differentiation strategies into significant performance improvements. Implications: Managers should integrate innovation efforts with strategic differentiation, and policymakers should create supportive environments to foster innovation in the Nepalese commercial banking sector.